PENINGKATAN EFISIENSI ALIRAN PRODUKSI BAGLOG JAMUR TIRAM MELALUI PENDEKATAN LEAN THINKING DAN SIMULASI - Marcellino Hanafi, Christ
Indonesia’s oyster mushroom national production has been drastically decreasing since 2017, which is quite regrettable considering the potential export commodity it represents. PT Gaya Green Srikandi is one of the companies that focuses on oyster mushroom farming. As of now, the company has experienced problems with their production performance due to inconsistency in mushroom substrate production (baglog), making them unable to fulfill the demand. This study aims to solve the problem within the production process by identifying waste with lean thinking and proposing improvements with simulation modeling. Assessing PT Gaya Green Srikandi’s current production system is done using a simulation model that will be constructed using Flexsim. This simulation will need to be verified, validated, and experimented with, such as reducing the number of operators and increasing the production capacity, to determine more efficient production system parameters. Based on the experiment results, a proposed production system will be designed. The proposed production system will incorporate a buffer at logging stations and introduce a new type of operator called the runner operator, whose main objective is to transport the WIP into the system. Based on the simulation model run, the proposed production system is able to increase efficiency based on system input and operator utilization. The proposed production system is able to reduce operator input by 1 operator and increase the utilization of the operator by an average 10% higher than the current production system. Investment analysis shows that the benefits of implementing the proposed systems far outweigh the costs incurred.